Unconventional oil and gas resources handbook : evaluation and development - Ma, Y. Zee; Holditch, Stephen A. (Gulf Professional Publishing in an imprint of Elsevier, 2015)
Annotation 'Unconventional Oil and Gas Resources Handbook' is a must-have, helpful handbook that brings a wealth of background information to the engineer and geologist alike. Bridging between subsurface and production, the handbook extends your reservoir's potential by providing multiple layers of methods to lead you to a better defined reservoir. Better reservoir knowledge and more sophisticated technology are making unconventional resources economically possible, but for young and even experienced engineers, this kind of reservoir is new and complex, making identification and characterization difficult and confusing.
Includes index.
Keywords: Petroleum engineering -- Handbooks, manuals, etc.; Petroleum -- Prospecting -- Handbooks, manuals, etc.; elektronické knihy; electronic books